METODE TABSYIR DALAM PENDIDIKAN ISLAM DAN URGENSINYA DALAM PENDIDIKAN MODERN - Rahimi Rahimi (SCAD Independent, 2014)
In education, the methods are an essential and have an urgent position (important), especially to achieve the goals and learning objectives. Methods